Plant Growth Promotion and Biocontrol by Endophytic and Rhizospheric Microorganisms From the Tropics: A Review and Perspectives - Lacava, Paulo Teixeira; Bogas, Andréa Cristina; Cruz, Felipe de Paula Nogueira (Frontiers in Sustainable Food Systems, 2022)
Currently, the tropics harbor a wide variety of crops to feed the global population. Rapid population expansion and the consequent major demand for food and agriculture-based products generate initiatives for tropical forest deforestation, which contributes to land degradation and the loss of macro and micronative biodiversity of ecosystems. Likewise, the entire dependence on fertilizers and pesticides also contributes to negative impacts on environmental and human health. To guarantee current and future food safety, as well as natural resource preservation, systems for sustainable crops in the tropics have attracted substantial attention worldwide. Therefore, the use of beneficial plant-associated microorganisms is a promising sustainable way to solve issues concerning modern agriculture and the environment. Efficient strains of bacteria and fungi are a rich source of natural products that might improve crop yield in numerous biological ways, such as nitrogen fixation, hormone production, mobilization of insoluble nutrients, and mechanisms related to plant biotic and abiotic stress alleviation. Additionally, these microorganisms also exhibit great potential for the biocontrol of phytopathogens and pest insects. This review addresses research regarding endophytic and rhizospheric microorganisms associated with tropical plants as a sustainable alternative to control diseases and enhance food production to minimize ecological damage in tropical ecosystems.